BISH–QVCO: A Low–Power, Low–Phase noise Bulk–Injected Super–Harmonic coupling QVCO. (May 2021) - Jafari, Bahram; Tavakoli, Javad; Sheikhaei, Samad
Abstract: In this paper, a novel method of Super–Harmonic coupling is proposed to generate quadrature outputs. In this method, by direct connection of all switching transistors bulk terminals, a second harmonic current is injected from each one of the I/Q oscillators to the other. Therefore, the proposed circuit is called Body–Injected Super–Harmonic coupling (BISH–) QVCO. The quadrature operation of the proposed circuit is mathematically proven and certified by simulations. In addition, through a detailed analysis, closed–form expressions are derived for the output phase noise and phase error. To have a fair performance evaluation of the proposed topology, the proposed BISH-QVCO, and the conventional P–QVCO are designed and simulated in 0.18 ​μm RF-CMOS technology with 3.22–3.64 ​GHz oscillation frequency (12.25% tuning range), a power supply of 1.8V, and the same power consumption of 3.85 ​mW. The quality factor of the tank circuits is calculated as 9.2. Post layout simulation results predict phase noise of −122.3dBc/Hz at 1 ​MHz offset from 3.64 ​GHz oscillation frequency that presents 4.1 ​dB and 2.7 ​dB phase noise improvements compared to the conventional P–QVCO and simple LC VCO, respectively. The maximum I and Q outputs phase error due to a 2% tank capacitor mismatch is 7°. A FOMT of 189.4 ​dB is achieved for the proposed QVCO. Also, the proposed method is capable of generating multi– phase outputs, which can be ranked among the well-performing ones. Graphical abstract: Image 1